Marketing Strategy for Processed Smoked Fish at Sipujuk Farm Ikur Koto Panjang, Koto Tangah, Padang West Sumatra - Srilona, Mersy Applika; Warningsih, Trisla; Yulinda, Eni (Fakultas Perikanan dan Kelautan Universitas Riau, 2023)
This research was conducted in May 2022 in Ikur Koto Panjang Village, Koto Tangah District, Padang City. This research aims to analyze internal and external factors and marketing strategies in Sipujuk Farm; the internal factors in question are strengths and weaknesses, while external factors are opportunities and threats to the smoked fish marketing strategy at Sipujuk Farm. The method used in this research is the survey method by conducting interviews directly in the field and collecting data by filling out questionnaires. Respondents totaled nine people who were taken by purposive sampling with predetermined criteria. Data analysis techniques using SWOT analysis try to describe and analyze the level of advantages, disadvantages, opportunities, and threats as well as what kind of marketing strategies should be carried out by businesses in Sipujuk Farm Padang in marketing them. The results of this study are from the results of the analysis of internal factors obtained weighting score value on smoked fish business Sipujuk Farm Padang, namely for internal 2.89 and analysis of external factors received weighting score value on smoked fish business Sipujuk Farm Padang, namely 1.96. The strategy prioritized in the Sipujuk Farm smoked fish business is in the position I (aggressive strategy) to grow and develop, namely the SO strategy. These strategies include Maintaining product quality, expanding target marketing, utilizing certain parties when visiting to introduce smoked fish businesses both on social media and the real world, product quality that has the characteristic of being a differentiator from other smoked fish and a place of business that carries out overall fishery activities and maintains the image or image of the Sipujuk Farm Padang smoked fish business.